Heat transfer with chemical reaction in wall heated packed bed reactor - Subbarao, D. (Trans Tech Publications Ltd, 2014)
Information on wall heat transfer to packed bed reactors operating with exothermic or endothermic reactions is scarce. Overall wall heat transfer coefficients in a packed bed reactor in presence of an endothermic reaction are measured and observed to be smaller than the expected in the absence of reaction. This observation is in contrast with the reported observations with exothermic reactions in packed beds. A model equation based on energy balance is presented to explain the observations. Â© 2014 Trans Tech Publications, Switzerland.